Biodiesel produced from transesterification of palm oil using NaOH-treated activated carbon and pyrolytic char of used tires as catalysts - Chana, Khulanuttha; Chen, Bing Hung; Na-Ranong, Duangkamol (My University, 2025)
Biodiesel produced from catalyzed transesterification of palm oil with methanol using NaOH-treated carbonaceous catalysts was studied and reported. Particularly, effect of the carbonaceous support, i.e. activated carbon (AC) and pyrolytic char of end-of-life used tire (TPC), on the yield of biodiesel was investigated. The resultant yield of biodiesel near 98.5 % could be attained from transesterification reactions conducted with a catalyst loading at 5 wt% of palm oil initially used, under a molar ratio of methanol/oil at 21/1, at 65°C and 180 min for reaction temperature and time. The kinetics of the transesterification reaction could be fitted satisfactorily with the pseudo first-order model. The Arrhenius behavior was observed from the temperature-dependent rate constants, leading to an activation energy at 111.2 kJ/mol if AC-supporting catalyst was used. Both AC and TPC-supporting catalysts could produce biodiesel with a yield greater than 90 % even after the fourth cycles of catalyzed transesterification reactions. Notably, the feasibility in the upcycling of TPC as catalyst support was demonstrated in this work.
Keywords: Activated carbon; Biodiesel; Fatty acid methyl ester (FAME); Heterogeneous catalyst; Pyrolytic char; Used tire; Waste tire upcycling